Ninein, a candidate gene for ethanol anxiolysis, shows complex exon-specific expression and alternative splicing differences between C57BL/6J and DBA/2J mice - Gnatowski, E. R.; Jurmain, J. L.; Dozmorov, M. G.; Wolstenholme, J. T.; Miles, M. F. (Frontiers in Genetics, 2024)
Ethanol's anxiolytic actions contribute to increased consumption and the development of Alcohol Use Disorder (AUD). Our laboratory previously identified genetic loci contributing to the anxiolyticlike properties of ethanol in BXD recombinant inbred mice, derived from C57BL/6J (B6) and DBA/2J (D2) progenitor strains. That work identified Ninein (Nin) as a candidate gene underlying ethanol's acute anxiolytic-like properties in BXD mice. Nin has a complex exonic content with known alternative splicing events that alter cellular distribution of the NIN protein. We hypothesize that strain-specific differences in Nin alternative splicing contribute to changes in Nin gene expression and B6/D2 strain differences in ethanol anxiolysis. Using quantitative reversetranscriptase PCR to target specific Nin splice variants, we identified isoform-specific exon expression differences between B6 and D2 mice in prefrontal cortex, nucleus accumbens and amygdala. We extended this analysis using deep RNA sequencing in B6 and D2 nucleus accumbens samples and found that total Nin expression was significantly higher in D2 mice. Furthermore, exon utilization and alternative splicing analyses identified 8 differentially utilized exons and significant exon-skipping events between the strains, including 3 novel splicing events in the 3' end of the Nin gene that were specific to the D2 strain. Additionally, we document multiple single nucleotide polymorphisms in D2 Nin exons that are predicted to have deleterious effects on protein function. Our studies provide the first in-depth analysis of Nin alternative splicing in brain and identify a potential genetic mechanism altering Nin expression and function between B6 and D2 mice, thus possibly contributing to differences in the anxiolytic-like properties of ethanol between these strains. This work adds novel information to our understanding of genetic differences modulating ethanol actions on anxiety that may contribute to the risk for alcohol use disorder.